Management Control Systems, Decision-Making, and Innovation Development : The CDI Model - Szutowski, Dawid (Taylor & Francis, 2021)
Management Control Systems, Decision-Making, Innovation Development, CDI model, transactive memory system, decision effectiveness
English
Keywords: Business & management; Management Control Systems, Decision-Making, Innovation Development, CDI model, transactive memory system, decision effectiveness